2011
DOI: 10.4028/www.scientific.net/amr.409.520
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Magnetic Properties of Mn-Zn Ferrite Synthesized by Glycine-Nitrate Auto-Combustion Process

Abstract: Manganese-Zinc ferrites belong to the group of soft ferrite materials characterized by high magnetic permeability and low power loses. These materials are mainly used as cores for inductors, transformers, recording heads and noise filters among others. In this study, nanocrystalline Mn-Zn ferrite with the chemical formula Mn1-xZnxFe2O4withx=0.2, 0.4, 0.6, 0.8 has been successfully synthesized by glycine-nitrate auto-combustion process using glycine as a fuel and nitrates as oxidants. The structures and magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…SEM is widely used for it but TEM is better than SEM because of poor resolution of SEM. AFM is a technique that can be used in different conditions like air, vacuum, liquid and moist conditions.Winiarska et al [205] observed that the TEM gave core shell type structure formation.Mirsekari et al [204] found from the SEM micrographs that the morphology of MnZn ferrite was porous, sponge like and agglomerated with an average particle size of 2µm. Anwar et al [9] observed from the SEM micrographs that the particles were spherical in shape.Gabal et al [206] studies showed that TEM morphology showed very strong agglomeration of the cubic particles, having some particles in one line.…”
Section: Morphological Structurementioning
confidence: 99%
See 3 more Smart Citations
“…SEM is widely used for it but TEM is better than SEM because of poor resolution of SEM. AFM is a technique that can be used in different conditions like air, vacuum, liquid and moist conditions.Winiarska et al [205] observed that the TEM gave core shell type structure formation.Mirsekari et al [204] found from the SEM micrographs that the morphology of MnZn ferrite was porous, sponge like and agglomerated with an average particle size of 2µm. Anwar et al [9] observed from the SEM micrographs that the particles were spherical in shape.Gabal et al [206] studies showed that TEM morphology showed very strong agglomeration of the cubic particles, having some particles in one line.…”
Section: Morphological Structurementioning
confidence: 99%
“…Praveena et al [179]observed that the value of saturation magnetization (M s ) increased from 53.33Am 2 /Kg to 78.26Am 2 /Kg with increase in zinc content and then decreased to 10.74Am 2 /kg if zinc content is further increased. From the hysteresis curves Mirsekari et al [204] observed that the saturation magnetization decreased from 69 to 34 emu/g.Gabal et al [186]observed the value saturation magnetization M s increased from 32.9emu/g to 37.6emu/g,then decreasedto 25.9emu/g and again increased to 43.7emu/g.The value of saturation magnetization was found to be 27.7emu/g in Phong [112] experiment showed the properties of superspin glass and supermagnetismbehavior.The study of Zapata [30] showed that the M s value decreased from 36.22emu/g to 30.78emu/g with increase in Zn concentration. This was due to the fact that increased Zn content decreased the ferric ions on the A sites and this reduced the A-B interaction.…”
Section: Saturation Magnetizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among magnetic nanoparticles available, nanosized Mn-Zn ferrite materials not only have unique size-dependent physical and chemical properties compared with their bulk counterparts but have also emerged as potential candidates for hyperthermia application, because of their suitable T C (340 K) and high stability of permeability with temperature and time. 12 Several methods are used to produce Mn-Zn ferrite nanoparticles, [13][14][15][16][17][18][19] the most common being co-precipitation, hydrothermal precipitation, sol-gel synthesis, and combustion synthesis.…”
Section: Introductionmentioning
confidence: 99%